AB0300 Medium and large sized joint involvement is more associated with functional disability than small joint destruction in 102 active advanced rheumatoid arthritis patients treated with non-biological dmards (cross-sectional study). (23rd January 2014) - Katayama, K.; Okubo, T.; Sato, T.
Abstract : Background: It has been reported that small joint destruction (hands and feet) affects damage (DAM)-HAQ index, whereas disease activity worsens activity (ACT)-HAQ index caused by inflammation. Clinically, in advanced rheumatoid arthritis (RA) patients, not only small joint destruction but medium and large (M-L) sized joint destruction appear to be associated with HAQ, especially DAM-HAQ index. However, little is known relationship between M-L sized joint destruction and functional disability in RA. Objectives: To identify whether M-L sized joint destruction affects functional disability in advanced RA patients treated with non biological (non-Bio) DMARDs. Methods: Active advanced 102 RA patients treated with non-Bio DMARDs were analyzed and patients who were treated with biologics were excluded. Patients were divided into three groups according to the score of modified HAQ (m-HAQ) index: the low HAQ group (0.5 ≥ mHAQ: HAQ remission, mean: 0.16, n=39), the medium HAQ group (1 ≥ mHAQ >0.5, mean: 0.81, n=27), and the high HAQ group (mHAQ >1, mean: 1.66, n=36). Clinical factors were compared among three groups and associations between mHAQ index and clinical factors were investigated. Clinical factors were as follows: Sex, Age, disease duration, dosage of PSL, DAS28-ESR, RF, MMP3, Ochi's RA classification (1), bone mineral density (hand, lumber spine and femoral neck) measured by dual X ray absorptiometry (DXA), Larsen grade measured by X ray (finger, wrist and toe), number of symptomatic M-L sized joints. Results: Patient baseline demographics were described as follows: mean age: 62.4year; RA disease duration, 10.4 year, DAS28-ESR, 5.35; modified Larsen score:1.70 and modified HAQ index:0.86. In the low, middle and high HAQ groups, mean DAS28 was 4.69, 5.25 and 6.16, mean modified Larsen scores (finger, wrist and toe) for small joints were 1.55, 1.77 and 1.81 and mean number of affected M-L sized joints were 3.2, 4.8 and 6.3, mean hand BMD was 0.29, 0.30and 0.26 g/cm 2, respectively. Significant difference in m-HAQ index was observed among HAQ groups (P<0.0001). Significant difference was detected as follows: disease duration (high vs. low, P=0.03); DAS28-ESR (high vs. medium and high vs. low, P<0.0001); finger Larsen score (high vs. low, P=0.021); symptomatic M-L sized joints (high vs. medium, medium vs. low, P<0.0001). According to the Ochi's classification, the least erosive subset was higher in low HAQ group than in other groups, and the mutilating disease was higher in high HAQ group than in other groups (P<0.001). Significant difference was not observed in any other clinical factors between HAQ groups. Finally, modified HAQ index correlated with number of M-L sized joints with clinical symptom (R=0.54, P<0.001), DAS28-ESR (R=0.54, P<0.001), but not associated with finger Larsen score (R=0.31, P<0.01) and wrist Larsen score (R=0.096, P=0.35). Conclusions: DAS28-ESR and M-L sized joint involvement were more important factors affecting HAQ index in active advanced RA treated with non-Bio DMARDs than small joint damage. To clarify this, further chronological study may be required. References: Ochi, T et al. Natural course of joint destruction and fluctuation of C1q levels in patients with rheumatoid arthritis. Arthritis Rheum 1988:31.37-43 Disclosure of Interest: None Declared